Influence of Weaving Loom Setting Parameters on Changes of Woven Fabric Structure and Mechanical Properties - Aušra ADOMAITIENĖ; Greta RAVINIENĖ; Eglė KUMPIKAITĖ (Medžiagotyra, 2011)
During the manufacturing of fabric of different raw material there was noticed, that after removing the fabric from weaving loom and after stabilization of fabric structure, the changes of parameters of fabric structure are not regular. During this investigation it was analysed, how weaving loom technological parameters (heald cross moment and initial tension of warp) should be chosen and how to predict the changes of fabric structure parameters and its mechanical properties. The dependencies of changes of half-wool fabric structure parameters (weft setting, fabric thickness and projections of fabric cross-section) and mechanical properties (breaking force, elongation at break, static friction force and static friction coefficient) on weaving loom setting parameters (heald cross moment and initial warp tension) were analysed. The orthogonal Box plan of two factors was used, the 3-D dependencies were drawn, and empirical equations of these dependencies were established. http://dx.doi.org/10.5755/j01.ms.17.4.780